Differential Neural Processing of Social Exclusion and Inclusion in Adolescents with Non-Suicidal Self-Injury and Young Adults with Borderline Personality Disorder - Brown, Rebecca C.; Plener, Paul L.; Groen, Georg; Neff, Dominik; Bonenberger, Martina; Abler, Birgit (Frontiers in Psychiatry, 2017)
Introduction: Non-suicidal self-injury (NSSI) is a symptom of Borderline Personality Disorder (BPD). However, NSSI often occurs independently of BPD. Altered neural processing of social exclusion has been shown in adolescents with NSSI and adults with BPD with additional alterations during social inclusion in BPD patients. Aims of this study were to investigate differences in neural processing of social inclusion and exclusion situations between adolescents with NSSI and young adults with BPD and NSSI. Methods: Using fMRI, neural processing of positive and negative social situations (paradigm: ‘Cyberball’) was explored. Participants were 14 adolescents with NSSI, but without BPD (Mage=15,4; SD=1,9), 15 adults with BPD and NSSI (Mage=23,3; SD=4,1), as well as 15 healthy adolescents (Mage=14,5; SD=1,7) and 16 healthy adults (Mage=23,2; SD=4,4). Results: Behavioral results showed enhanced feelings of social exclusion in both patient groups as compared to healthy controls but only the NSSI group showed enhanced activation during social exclusion vs. inclusion compared to the other groups. While both, NSSI and BPD group showed enhanced activation in the ventral anterior cingulate cortex during social exclusion as compared to their age-matched controls, enhanced activation during social inclusion as compared to a passive watching condition was mainly observed in the BPD group in the dorsolateral and dorsomedial prefrontal cortex, and the anterior insula. Discussion: While neural processing of social exclusion was pronounced in adolescents with NSSI, BPD patients also showed increased activity in a per se positive social situation. These results might point towards a higher responsiveness to social exclusion in adolescents with NSSI, which might then develop into a generalized increased sensitivity to all kind of social situations in adults with BPD.